STRATEGI PEMASARAN BUS AKAP JALUR JAWA – BALI MELALUI PENERAPAN CHSE PADA MASA NORMALISASI COVID-19 - Made Bambang Adnyana (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Transportation during the covid-19 pandemic, adjusts to regulations from the Ministry of Transportation, namely SE 94 of 2021 regarding instructions for carrying out domestic travel by land transportation modes during the Covid-19 pandemic. One of the points of the circular letter is that the limitation of passenger capacity on public and private transportation is at most 70% by means of physical distancing for areas located at PPKM Level 3 and Level 2. Areas in PPKM Level 3 and Level 2 are no exception. the province of Bali and several cities on the island of Java. These restrictions affect the number of public transport passengers, one of which is the inter-city inter-provincial night bus (AKAP). Bus is a mode of transportation that is often used by the general public and affordable for all people, the use of this mode of land public transportation is to take passengers from one city to another. The COVID-19 pandemic is a time when bus entrepreneurs have to rack their brains to continue to survive and bring new innovations to adapt to the current situation and conditions. In mid-2020, many bus entrepreneurs presented the latest creativity or innovation to attract the attention of passengers on long trips, one of which was the Social Distancing Class. This class is the latest concept for bus operator entrepreneurs to meet the needs of passengers who are still worried about the spread of the COVID-19 virus. The concept of Social Distancing Class on the Java-Bali night bus is expected to meet the CHSE (Clean, Healthy, Save and Environment) requirements or criteria promoted by the Ministry of Tourism and Creative Economy. This study uses a descriptive qualitative approach and the SWOT method (Strength, Weakness, Opportunity, Threats). This method is expected to find out how much the strengths, weaknesses, opportunities and challenges of night buses, especially intercity buses between Java-Bali provinces, apply the concept of Social Distancing Class. Keyword : Marketing Mix, SWOT, Social Distancing Class, CHSE, Bus AKAP